Hydrogeochemical Characteristics of the Suleymanli Thermomineral Waters, Kahramanmaras, Turkey - Bozdag, S. (Asian Journal of Chemistry, 2010)
The present study was carried out to assess the hydrogeochemical composition of the Suleymanli (Kahramanmaras, Turkey) thermomineral springs. The springs issue along fault zones and their temperatures ranks between 40 and 45 ºC and they are classified as hot water. Chemical analysis indicate a chemical composition of Mg > Ca > (Na + K) and HCO3 > SO4 > Cl. The results of chemical and heavy metal analysis are evaluated according to the World Health Organisation and Turkish Standards. As a conclusion, the Suleymanli hot waters can be drinkable and usable for health treatment.